Diatomic metal complex / CdS nanorod composite photocatalyst as well as preparation method and application thereof
By recombining the diatomic metal complex Fe2LCl2 with CdS nanorods, the problems of the susceptibility of CdS nanorod photocatalysts and poor electron hole separation capabilities are solved, and the effect of improving photocatalytic activity and stability is achieved.
Patent Information
- Application Number
- CN202411593072.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Existing CdS nanorod photocatalysts are susceptible to photocorrosion, have poor electron hole separation capabilities, high cost and rarity limitations, and single-atom catalysts may have problems with insufficient active sites.
The diatomic metal complex Fe2LCl2 is used to recombinate it with CdS nanorods, and CdS nanorods are synthesized by hydrothermal reaction, and the diatomic metal complex is synthesized by Schiff base reaction. The two are physically recombined to form a composite photocatalyst.
Effectively prevent the rapid recombination of photogenerated electrons and holes, avoid photocorrosion of CdS, improve photocatalytic activity, enhance the stability of the catalyst, reduce activation energy, and improve the formic acid decomposition reaction activity.
Smart Images

Figure CN119680642A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically belongs to the technical field of powder photocatalytic materials, and specifically relates to a diatomic metal complex / CdS nanorod composite photocatalyst and a preparation method and application thereof. Background Art
[0002] Due to the increasing global energy consumption, the development of alternatives to fossil fuels is highly desirable. Synthesis gas has proven to be a useful fuel for the future, as it can be used directly in internal combustion engines or converted into liquid fuels via the Fischer-Tropsch process. Moreover, synthesis gas is a feedstock for the chemical industry to produce synthetic products. Currently, most of the synthesis gas production comes from fossil fuel sources and requires high temperature and pressure conditions. Formic acid can be used as a reproducible source for synthesis gas production due to its low toxicity and high weight content of hydrogen and carbon. Moreover, formic acid is a liquid at ambient temperature and does not require special handling conditions for transportation and storage. During the decomposition of formic acid, H2, CO and some carbon dioxide can be produced. The released carbon dioxide can be recycled to produce formic acid under appropriate conditions, resulting in a sustainable and viable cycle for the storage and release of chemical energy.
[0003] Solar energy is environmentally friendly, inexhaustible, and emission-free. Therefore, photocatalytic fatty acid dehydrogenation at room temperature and under sunlight has attracted great attention. Different types of catalysts have been used to study the efficient photocatalytic reaction of formic acid, such as semiconductors, organic polymers, single-atom catalysts, molecular complexes, etc. Generally, CdS nanorods are considered to be a very promising semiconductor catalyst due to their low cost, appropriate redox ability, and high photocatalytic activity. However, they have certain limitations in the photocatalytic decomposition of formic acid due to their susceptibility to photocorrosion and poor electron-hole separation ability. Co-catalysts can further solve this problem and improve the activity and stability of CdS nanorods. Many noble metals have been applied to the photocatalytic decomposition of formic acid due to their synergistic catalytic effects, such as Ir-Ru complexes, Pd, Pt, AuPd, and AgPd. However, the high cost and rarity of noble metals limit the cost and feasibility of experiments, and the development of noble metal-free photocatalytic systems should be more in line with the concept of sustainable development. Fe-salen with a noble metal-free homogeneous single-atom configuration can be used as a low-cost and efficient photocatalytic FA decomposition catalyst. Although such single-site catalysts show potential advantages, single-atom catalysts may suffer from the problem of insufficient neighboring sites.
[0004] Therefore, the above-mentioned prior art solutions have the following defects: the existing CdS nanorod photocatalysts are susceptible to photocorrosion and have poor electron-hole separation ability, and have certain limitations in the photocatalytic decomposition of formic acid. The high cost and rarity of the precious metal catalyst system limit the cost and feasibility of the experiment, and the non-precious metal single-atom catalysts may have insufficient active sites. Summary of the invention
[0005] Based on the above-mentioned shortcomings of the prior art that CdS nanorods are susceptible to photocorrosion and have poor electron-hole separation ability, the high cost and rarity of precious metal catalyst systems, and the possible lack of active sites in non-precious metal single-atom catalysts, one of the objects of the present invention is to provide a diatomic metal complex / CdS nanorod composite photocatalyst that can effectively prevent the rapid recombination of photogenerated electrons and holes, and can also effectively avoid CdS from being corroded by light.
[0006] To achieve the above object, the present invention adopts the following technical scheme, a method for preparing a diatomic metal complex / CdS nanorod composite photocatalyst, comprising the following steps:
[0007] S1. FeCl2·4H2O and methanol are placed in a nitrogen reflux container, and a boiling methanol solution containing 1,3-propylenediamine is added, and a boiling methanol solution containing 2,6-diformyl-4-methylphenol is added to obtain a mixed solution;
[0008] S2. The mixed solution was heated in an oil bath by condensation reflux. After the reaction was completed, the crystalline solid was collected by suction filtration and washed with cold methanol to obtain the final product Fe2C 26 H 34 N4O4Cl2, referred to as Fe2LCl2;
[0009] S3, after mixing CdS nanorods and Fe2LCl2, add ethanol, stir the reaction and then dry, and collect the composite product Fe2-CdS.
[0010] Further improvement of diatomic metal complex / CdS nanorod composite photocatalyst:
[0011] Preferably, the preparation method of the CdS nanorods in step S3 is as follows: cadmium nitrate tetrahydrate and thiourea are added to a Teflon-lined high-pressure reactor filled with ethylenediamine as a solvent, and the high-pressure reactor is sealed and reacted in an oven after stirring. After the reaction is completed, the reaction is cooled to room temperature, washed with water and ethanol to obtain a precipitate, and dried to obtain CdS nanorods.
[0012] Preferably, the concentration of cadmium nitrate tetrahydrate added to ethylenediamine is 0.0385-0.1155 g / ml, the concentration of thiourea added to ethylenediamine is 0.0385-0.1155 g / ml, and the mass ratio of cadmium nitrate tetrahydrate to thiourea is (0.5-3):1.
[0013] Preferably, during the preparation of CdS nanorods, the stirring temperature is 20-50° C., and the time is 20-60 min; the reaction temperature is 140-160° C., and the time is 24-72 h.
[0014] Preferably, the amount of FeCl2·4H2O added to methanol in step S1 is 0.008-0.064 g / ml.
[0015] Preferably, in the boiling methanol solution containing 1,3-propylenediamine, the addition amount of 1,3-propylenediamine is 0.0368-0.292 ml / ml; in the boiling methanol solution containing 2,6-diformyl-4-methylphenol, the concentration of 2,6-diformyl-4-methylphenol is 0.0068-0.0526 g / ml; when preparing the mixed solution, the quantitative relationship between FeCl2·4H2O and 1,3-propylenediamine and 2,6-diformyl-4-methylphenol is 1:1:1.
[0016] Preferably, the temperature of the oil bath heating in step S2 is 50-80°C and the time is 2-6h; the time of the stirring reaction in step S3 is 6-10h and the drying temperature is 60-80°C.
[0017] Preferably, in step S3, CdS nanorods and Fe2LCl2 are mixed in a mass ratio of 1:1-4:1, and ethanol is added until the concentration of CdS nanorods in ethanol is 3-5 mg / ml.
[0018] The second object of the present invention is to provide a diatomic metal complex / CdS nanorod composite photocatalyst prepared by any of the preparation methods described above, the composite photocatalyst consists of CdS nanorods and diatomic metal complexes loaded on the surface of the CdS nanorods; the CdS nanorods have a length of 1-3 μm and a hexagonal crystal structure; the diatomic metal complex is in block form, specifically a diiron atom complex; the mass ratio of CdS nanorods to the diatomic metal complex is 2:1, and the two are physically composited with interface interaction.
[0019] The third object of the present invention is to provide a use of the above-mentioned diatomic metal complex / CdS nanorod composite photocatalyst for photocatalytic decomposition of formic acid to produce hydrogen and carbon monoxide.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1) The present invention provides a diatomic metal complex / CdS nanorod composite photocatalyst, wherein the main structure of the composite material is CdS nanorods, and the surface is wrapped by diatomic metal complexes, and the length of the CdS nanorods is 1-3 μm, and the structure is hexagonal. In the process of photocatalytic formic acid decomposition, the CdS nanorods and the complexes interact on the surface, and there is an inherent electric field between the CdS nanorods and the diatomic metal complexes. The electrons in the middle CdS nanorods are excited, which promotes the transfer of outer electrons toward the diatomic metal complex, resulting in the rapid transmission of photogenerated carriers, ensuring the effective separation and utilization of photogenerated electrons and holes, thereby further enhancing the photocatalytic activity. It can effectively prevent the rapid recombination of photogenerated electrons and holes, and can also effectively prevent CdS from being corroded by light.
[0022] 2) The present invention provides a method for preparing a diatomic metal complex / CdS nanorod composite photocatalyst, firstly synthesizing CdS nanorods by hydrothermal reaction, then synthesizing a diatomic metal complex by Schiff base reaction under oil bath heating and condensation reflux, placing the two in a beaker and adding ethanol, stirring evenly and drying, to obtain a diatomic metal complex and CdS nanorod photocatalytic composite material. The advantages of this product are mainly divided into two aspects:
[0023] First, the co-catalysts used for formic acid decomposition are usually noble metal catalysts, such as Ir-Ru complexes, Pd, Pt, AuPd and AgPd, etc. However, the high cost and rarity of noble metals limit the cost and feasibility of the experiment. The homogeneous single-atom Fe-salen in the noble metal-free photocatalytic system can be used as a low-cost and efficient photocatalytic FA decomposition catalyst, but the single-atom catalyst may have the problem of insufficient adjacent sites. The diatomic catalyst Fe2LCl2 as a co-catalyst has two metal active sites, which can provide effective surface reaction active sites, making the surface catalytic reaction easy to occur and improving the reaction activity.
[0024] Finally, the photocatalytic formic acid decomposition performance test of the photocatalytic material composited with CdS nanorods generally produces only hydrogen, without carbon monoxide products, but the photocatalytic formic acid decomposition performance test of the photocatalytic system after Fe2LCl2 is used as a co-catalyst and composited with CdS nanorods produces synthesis gas, i.e., hydrogen and carbon monoxide. Moreover, Fe2LCl2 acts as a co-catalyst, and further inhibits the recombination of photogenerated electrons and holes through the migration of photogenerated charges to the co-catalyst; it can accelerate the photocatalytic formic acid decomposition reaction, avoid photocorrosion oxidation of the photocatalytic system, improve the stability of the photocatalytic system, reduce the activation energy of the catalytic reaction, and improve the reaction activity of photocatalytic formic acid decomposition. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1These are the scanning electron microscope images of the CdS nanorods obtained in Preparation Example 1 of the present invention and the lattice fringe pattern of the CdS nanorods; wherein, Figure (a) is the scanning electron microscope image, and Figure (b) is the lattice fringe pattern of the CdS nanorods.
[0026] Figure 2 This is a scanning electron microscope image of Fe2LCl2 prepared in Preparation Example 2 characterized by using a scanning electron microscope.
[0027] Figure 3 This is a scanning electron microscope image of the Fe2-CdS composite photocatalyst prepared in Example 1 characterized by using a scanning electron microscope.
[0028] Figure 4 This is a transmission electron microscope image of the Fe2-CdS composite photocatalyst prepared in Example 1 characterized using a transmission electron microscope.
[0029] Figure 5 These are electron microscope images of the Fe2-CdS composite photocatalyst prepared in Example 1 characterized by using a transmission electron microscope, wherein (a) is a transmission electron microscope image of a single Fe2-CdS composite photocatalyst, and (b) is a mapping image of a single Fe2-CdS composite photocatalyst.
[0030] Figure 6 The X-ray diffraction patterns of Preparation Examples 1, 2 and Example 1 were characterized using an X-ray diffractometer.
[0031] Figure 7 The X-ray diffraction patterns of Preparation Examples 2, 3, and 4 were characterized using an X-ray diffractometer.
[0032] Figure 8 These are the results of characterizing Preparation Example 2 and Example 1 using a Fourier transform infrared spectrometer.
[0033] Fig. 9 The X-ray photoelectron spectroscopy spectrum of Example 1 characterized by using an X-ray photoelectron spectrometer includes Fe 2p, Cd 3d, S2p, and Cl 2p spectra.
[0034] Fig.10 This is a total X-ray photoelectron spectrum of Example 1 characterized by using X-ray photoelectron spectroscopy.
[0035] Fig.11 It is the ultraviolet-visible spectroscopic spectra characterized by using an ultraviolet-visible spectrophotometer for Preparation Examples 1, 2 and Example 1.
[0036] Fig.12These are performance diagrams for optimizing the experimental conditions of Examples 2-5; wherein (a) is a diagram for optimizing the photocatalytic performance of Fe2LCl2 concentration, (b) is a diagram for optimizing the photocatalytic performance of pH value, and (c) is a diagram for optimizing the photocatalytic performance of formic acid concentration.
[0037] Fig.13 It is a performance comparison chart of Example 2 and Comparative Examples 1-4 for photocatalytic decomposition of formic acid to produce synthesis gas (H2+CO).
[0038] Fig.14 This is a performance cycle diagram of photocatalytic formic acid decomposition to produce synthesis gas (H2+CO) in Example 2. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0040] First, buy from the market or make it yourself:
[0041] Anhydrous formic acid; acetonitrile; methanol; sodium hydroxide; ferrous chloride tetrahydrate; cobalt nitrate hexahydrate; nickel chloride hexahydrate; 1,3-propylenediamine; 2,6-diformyl-4-methylphenol; 5-methylsalicylaldehyde; cadmium nitrate tetrahydrate; thiourea; ethylenediamine; isopropyl alcohol; deionized water.
[0042] Preparation Example 1
[0043] This embodiment provides a method for preparing CdS nanorods, and the specific steps are as follows:
[0044] S1. Weigh 4.62 g of cadmium nitrate tetrahydrate and 4.62 g of thiourea (mass ratio of 1:1), add them into a Teflon-lined autoclave filled with 60 mL of ethylenediamine (EDA) as a solvent, and stir at 40°C for 30 min.
[0045] S2, sealing the autoclave and maintaining it at 150° C. for 48 hours, cooling it to room temperature after the reaction is completed to obtain a reaction product;
[0046] S3. The reaction product is washed three times with water and ethanol and then dried to obtain CdS nanorods.
[0047] Preparation Example 2
[0048] This embodiment provides a method for preparing Fe2LCl2, and the specific steps are as follows:
[0049] S1. Place 0.56 g of FeCl2·4H2O and 17.5 mL of methanol (deoxygenated) into a 50 ml three-necked flask under nitrogen reflux;
[0050] S2, then sequentially adding 2.5 ml of a boiling methanol solution containing 0.356 ml of 1,3-propylenediamine and 17.5 ml of a boiling methanol solution containing 0.46 g of 2,6-diformyl-4-methylphenol to obtain a mixed solution;
[0051] S3, the mixed solution was heated to reflux in an oil bath at 65°C for 2 hours by condensation reflux, the crystalline solid was collected by suction filtration, and washed with cold methanol to obtain the final product Fe2C 26 H 34 N4O4Cl2, abbreviated as Fe2LCl2.
[0052] Preparation Example 3
[0053] This embodiment provides a method for preparing Co2L(NO3)2, and the specific steps are as follows:
[0054] S1. Place 0.233 g of Co(NO3)2·6H2O, 0.46 g of 2,6-diformyl-4-methylphenol and 10 mL of methanol (deoxygenated) into a 50 ml three-necked flask under nitrogen reflux;
[0055] S2, adding 2 ml of boiling methanol solution containing 0.0665 mL of 1,3-propylenediamine in turn to obtain a mixed solution;
[0056] S3, the mixed solution was refluxed by condensation, heated in an oil bath at 65°C for 3 hours, the crystalline solid was collected by suction filtration, and washed with cold methanol to obtain the final product Co2C 25 H 32 N6O 10 , referred to as Co2L(NO3)2.
[0057] Preparation Example 4
[0058] This embodiment provides a method for preparing Ni2LCl2, and the specific steps are as follows:
[0059] S1. 0.42 g NiCl2·6H2O, 0.195 g 2,6-diformyl-4-methylphenol, 0.0665 mL 1,3-propylenediamine and 25 mL isopropanol (deoxygenated) were placed in a 50 ml three-necked flask under nitrogen reflux;
[0060] S2, by condensation reflux, heating reflux in an oil bath at 82.5℃ for 18 hours, collecting the crystalline solid by suction filtration, and washing it with boiling methanol to obtain the final product Ni2C 24 H 30 N4O4Cl2, abbreviated as Ni2LCl2.
[0061] Preparation Example 5
[0062] This embodiment provides a method for preparing FeMCl, and the specific steps are as follows:
[0063] S1. Place 0.3 g FeCl2·4H2O and 25 mL methanol (deoxygenated) into a 50 ml three-necked flask under nitrogen reflux;
[0064] S2, then add 1 ml of a boiling methanol solution containing 0.125 ml of 1,3-propylenediamine and 8 ml of a boiling methanol solution containing 0.41 g of 5-methylsalicylaldehyde in sequence to obtain a mixed solution;
[0065] S2, by condensation reflux, reflux at 65 ° C for 2 hours, filter and collect the crystalline solid, and wash it with boiling methanol to obtain the final product FeC 19 H 20 N2O2Cl, referred to as FeMCl.
[0066] Example 1
[0067] This embodiment provides a method for preparing a diatomic metal complex / CdS nanorod composite photocatalyst, and the specific steps are as follows:
[0068] S1. Put 80 mg of the CdS nanorods prepared in Preparation Example 1 and 20 mg of the Fe2LCl2 prepared in Preparation Example 2 into a 50 ml beaker, add 20 ml of ethanol, and stir for 8 hours until the reaction is fully achieved;
[0069] S2. The reaction product is placed in an oven at 80° C. to dry, and the composite product Fe2-CdS is collected, which is a diatomic metal complex / CdS nanorod composite photocatalyst.
[0070] Example 2
[0071] This embodiment provides an application of a diatomic metal complex / CdS nanorod composite photocatalyst, and the specific steps are as follows:
[0072] S1. Measure 5 ml of acetonitrile, 15 ml of deionized water, and 1 ml of formic acid into a 50 ml reactor, and adjust the pH of the solution to 3.5 with sodium hydroxide; repeat the operation to prepare 6 portions in total, place them in the reactor and number them 1-6;
[0073] S2, take 2 mg of the CdS nanorods obtained in Preparation Example 1 and add them to the above reactor respectively. To adjust the concentration of Fe2LCl2, take 0 mg, 0.5 mg, 0.75 mg, 1 mg, 1.25 mg, and 1.5 mg of Fe2LCl2 obtained in Preparation Example 2 in the above reactor respectively, and seal the reactor;
[0074] S3. Place the reaction bottle on a stirring table, pass Ar gas for 30 min, and illuminate it under a 300W xenon lamp with a 420nm cutoff filter for 3 h to carry out photocatalytic formic acid decomposition reaction. Take 500 μl of the gas in the reactor every hour and inject it into the gas chromatograph to calculate the yields of H2 and CO.
[0075] This embodiment is to adjust the concentration of Fe2LCl2 to optimize the experimental conditions.
[0076] Example 3
[0077] This embodiment provides an application of a diatomic metal complex / CdS nanorod composite photocatalyst, and the specific steps are as follows:
[0078] S1. 5 ml of acetonitrile, 15 ml of deionized water and 1 ml of formic acid were respectively measured and placed in a 50 ml reactor; the operation was repeated to prepare 5 portions in total, which were placed in the reactor and numbered 1-5; to adjust the pH of the solution, sodium hydroxide was used to adjust the pH of the solution to 2.5, 3, 3.5, 4 and 4.5 respectively;
[0079] S2, taking 2 mg of the CdS nanorods obtained in Preparation Example 1 and 1 mg of the Fe2LCl2 obtained in Preparation Example 2 into the above reactor, and sealing the reactor;
[0080] S3. Place the reaction bottle on a stirring table, pass Ar gas for 30 min, and illuminate it under a 300W xenon lamp with a 420nm cutoff filter for 3 h to carry out photocatalytic formic acid decomposition reaction. Take 500 μl of the gas in the reactor every hour and inject it into the gas chromatograph to calculate the yields of H2 and CO.
[0081] This example is to adjust the pH of the solution to optimize the experimental conditions.
[0082] Example 4
[0083] This embodiment provides an application of a diatomic metal complex / CdS nanorod composite photocatalyst, and the specific steps are as follows:
[0084] S1. 5 ml of acetonitrile and 15 ml of deionized water were respectively measured and placed in a 50 ml reactor; the operation was repeated to prepare 5 portions in total, which were placed in the reactor and numbered 1-5; to adjust the formic acid concentration, 1 ml, 2 ml, 3 ml, 4.5 ml, and 6 ml of formic acid were respectively measured and placed in a 50 ml reactor, and the pH of the solution was adjusted to 3.5 with sodium hydroxide;
[0085] S2, taking 2 mg of the CdS nanorods obtained in Preparation Example 1 and 1 mg of the Fe2LCl2 obtained in Preparation Example 2 into the above reactor, and sealing the reactor;
[0086] S3. Place the reaction bottle on a stirring table, pass Ar gas for 30 min, and illuminate it under a 300W xenon lamp with a 420nm cutoff filter for 3 h to carry out photocatalytic formic acid decomposition reaction. Take 500 μl of the gas in the reactor every hour and inject it into the gas chromatograph to calculate the yields of H2 and CO.
[0087] This example is to adjust the formic acid concentration to optimize the experimental conditions.
[0088] Example 5
[0089] This embodiment provides an application of a diatomic metal complex / CdS nanorod composite photocatalyst, and the specific steps are as follows:
[0090] S1. 5 ml of acetonitrile, 15 ml of deionized water and 4.5 ml of formic acid were respectively measured and placed in a 50 ml reactor, and the pH of the solution was adjusted to 3.5 with sodium hydroxide;
[0091] S2, taking 2 mg of the CdS nanorods obtained in Preparation Example 1 and 1 mg of the Fe2LCl2 obtained in Preparation Example 2 into the above reactor, and sealing the reactor;
[0092] S3. Place the reaction bottle on a stirring table, pass Ar gas for 30 min, and illuminate it under a 300W xenon lamp with a 420nm cutoff filter for 3 h to carry out photocatalytic formic acid decomposition reaction. Take 500 μl of the gas in the reactor every hour and inject it into the gas chromatograph to calculate the yields of H2 and CO.
[0093] This embodiment is the optimal experimental condition obtained after optimizing the experimental conditions.
[0094] Comparative Example 1
[0095] This comparative example provides an application of a CdS photocatalyst, which specifically includes the following steps:
[0096] S1. 5 ml of acetonitrile, 15 ml of deionized water and 4.5 ml of formic acid were respectively measured and placed in a 50 ml reactor, and the pH of the solution was adjusted to 3.5 with sodium hydroxide;
[0097] S2, taking 2 mg of CdS nanorods obtained in Preparation Example 1 into a reactor, and sealing the reactor;
[0098] S3. Place the reaction bottle on a stirring table, pass Ar gas for 30 min, and illuminate it under a 300W xenon lamp with a 420nm cutoff filter for 3 h to carry out photocatalytic formic acid decomposition reaction. Take 500 μl of the gas in the reactor every hour and inject it into the gas chromatograph to calculate the yields of H2 and CO.
[0099] Comparative Example 2
[0100] This comparative example provides an application of a Co2-CdS composite photocatalyst, which specifically includes the following steps:
[0101] S1. Take 5 ml of acetonitrile, 15 ml of deionized water and 4.5 ml of formic acid respectively into a 50 ml reactor and adjust the pH of the solution to 3.5 with sodium hydroxide.
[0102] S2. Place 2 mg of CdS nanorods obtained in Preparation Example 1 and 1 mg of Co2L(NO3)2 obtained in Preparation Example 3 in a reactor, and seal the reactor.
[0103] S3. Place the reaction bottle on a stirring table, pass Ar gas for 30 min, and illuminate it under a 300W xenon lamp with a 420nm cutoff filter for 3 h to carry out photocatalytic formic acid decomposition reaction. Take 500 μl of the gas in the reactor every hour and inject it into the gas chromatograph to calculate the yields of H2 and CO.
[0104] Comparative Example 3
[0105] This comparative example provides an application of a Ni2-CdS composite photocatalyst, which specifically includes the following steps:
[0106] S1. Take 5 ml of acetonitrile, 15 ml of deionized water and 4.5 ml of formic acid respectively into a 50 ml reactor and adjust the pH of the solution to 3.5 with sodium hydroxide.
[0107] S2. Put 2 mg of CdS nanorods obtained in Preparation Example 1 and 1 mg of Ni2LCl2 obtained in Preparation Example 4 into a reactor, and seal the reactor.
[0108] S3. Place the reaction bottle on a stirring table, pass Ar gas for 30 min, and illuminate it under a 300W xenon lamp with a 420nm cutoff filter for 3 h to carry out photocatalytic formic acid decomposition reaction. Take 500 μl of the gas in the reactor every hour and inject it into the gas chromatograph to calculate the yields of H2 and CO.
[0109] Comparative Example 4
[0110] This comparative example provides an application of a Fe-CdS composite photocatalyst, which specifically includes the following steps:
[0111] S1. Take 5 ml of acetonitrile, 15 ml of deionized water and 4.5 ml of formic acid respectively into a 50 ml reactor and adjust the pH of the solution to 3.5 with sodium hydroxide.
[0112] S2. Take 2 mg of CdS nanorods obtained in Preparation Example 1 and 1 mg of FeMCl obtained in Preparation Example 5 into a reactor, and seal the reactor.
[0113] S3. Place the reaction bottle on a stirring table, pass Ar gas for 30 min, and illuminate it under a 300W xenon lamp with a 420nm cutoff filter for 3 h to carry out photocatalytic formic acid decomposition reaction. Take 500 μl of the gas in the reactor every hour and inject it into the gas chromatograph to calculate the yields of H2 and CO.
[0114] Performance Testing
[0115] The photocatalysts of the diatomic complexes and CdS nanorods prepared in Preparation Examples 1-5, Examples 1-5 and Comparative Examples 1-4 were subjected to structural characterization and performance testing. Figure 1-14 The CdS nanorods prepared in Preparation Example 1 were characterized using a scanning electron microscope, and the results were as follows Figure 1 As shown, Figure 1 (a) is a scanning electron microscope image of CdS nanorods, and (b) is a lattice fringe of CdS nanorods. Figure 1 It can be seen that the length of the CdS nanorods is 1-3 μm, with a hexagonal crystal structure, and the d value of the lattice fringes is 0.34 nm, which is confirmed to be the (001) crystal plane.
[0116] The Fe2LCl2 prepared in Preparation Example 2 was characterized by scanning electron microscopy. Figure 2 As shown. Figure 2 It can be seen that individual Fe2LCl2 is in large blocks.
[0117] The Fe2-CdS composite material prepared in Example 1 was characterized by scanning electron microscopy and transmission electron microscopy. Figure 3-5 As shown, Figure 3 Scanning electron microscopy of Fe2-CdS composite material. Figure 4 , 5 Transmission electron microscopy of Fe2-CdS composite material, Figure 5 (b) is the mapping image of Fe2-CdS composite material. Figure 3 It can be seen that the composite of Fe2LCl2 and CdS nanorods still has a rod-like morphology and does not change the original morphology of CdS nanorods. Figure 4 It can be seen that Fe2-CdS has a rod-like morphology, which further proves that the Fe2-CdS composite material was successfully prepared. A single composite sample was selected for transmission electron microscopy characterization. Figure 5 It can be seen that Cd, S, Fe, and Cl in the Fe2-CdS composite material are evenly distributed on the CdS rods, which once again verifies the successful preparation of the Fe2-CdS composite material.
[0118] Figure 6 The X-ray diffraction spectra of Preparation Examples 1, 2 and Example 1 were characterized using an X-ray diffractometer. Figure 6It can be seen that the X-ray diffraction spectra of the target products described in Preparation Examples 1 and 2 are consistent with the standard cards, proving that Preparation Examples 1 and 2 are successfully synthesized; the X-ray diffraction spectrum in Example 1 only shows the peak of CdS because the content of Fe2LCl2 added is relatively small.
[0119] Figure 7 The X-ray diffraction spectra of Preparation Examples 2, 3, and 4 were characterized using an X-ray diffractometer. Figure 7 It can be seen that the spectra of Preparation Examples 2, 3, and 4 are consistent with the theoretical X-ray diffraction spectra. Figure 1 The results show that the preparation examples 2, 3 and 4 were successfully synthesized.
[0120] Figure 8 The results of characterization of Preparation Example 2 and Example 1 using Fourier infrared spectrometer. Figure 8 It can be seen that the successful preparation of Preparation Example 1 and Example 1 both have CO bond peaks and no C=O bond peaks.
[0121] Fig. 9 The X-ray photoelectron spectrum of Example 1 is characterized by using X-ray photoelectron spectroscopy. Fig. 9 (a) The XPS Fe 2p spectrum shows that the Fe peak shifts 0.22 eV to the negative direction. Fig. 9 In the Cd 3d and S2p spectra in (b) and (c), it can be observed that the Cd and S peaks are shifted in the positive direction by 0.39 eV, indicating that the CdS nanorods and Fe2LCl2 interact with each other on the surface. There is an inherent electric field between the CdS nanorods and Fe2LCl2, which promotes the transfer of outer-shell electrons toward the complex, confirming that the increase in the production of syngas (H2+CO) is caused by Fe2LCl2, which promotes the photocatalytic decomposition of formic acid into H2 and CO.
[0122] Fig.10 This is the total X-ray photoelectron spectrum of Example 1 characterized by X-ray photoelectron spectroscopy. Fig.10 It can be seen that Example 1 contains C, O, N, Cd, S, Fe, and Cl elements.
[0123] Figure 6-10 The successful synthesis of diatomic and single-atom metal complexes and CdS nanorods, as well as the successful preparation of Fe2-CdS composites, were confirmed.
[0124] Fig.11 The UV-visible absorption spectra of Preparation Examples 1, 2 and Example 1 show that Fe2-CdS and CdS have similar absorption edges. Fig.11 It can be seen that the light absorption capacity of Fe2-CdS is significantly increased compared with CdS, especially in the λ>520nm region, which can be attributed to the strong inherent background absorption capacity of Fe2LCl2.
[0125] Fig.12 The figure is an optimization diagram of the experimental conditions for photocatalytic formic acid decomposition of Examples 2-5, indicating that the optimal experimental conditions are those of Example 5. Fig.12 It can be seen that the optimal implementation conditions for this experiment are 0.08mM Fe2LCl2, pH 3.5, and formic acid concentration 6M.
[0126] Fig.13 The photocatalytic formic acid decomposition performance comparison diagram of Examples 2 and 5 and Comparative Examples 1-4 shows that the Fe2-CdS composite material has the highest performance in photocatalytic formic acid decomposition to produce synthesis gas (H2+CO), with a H2 yield of 330 μmol -1 h -1 , CO yield was 141 μmol -1 h -1 .
[0127] Fig.14 The performance cycle diagram of Fe2-CdS composite material photocatalytic decomposition of formic acid to produce synthesis gas (H2+CO) is shown in Figure 2. Fig.14 It can be seen that the production of H2 and CO has been increasing steadily, indicating that the performance of the composite material is stable.
[0128] The above is a detailed description of the preferred embodiments of the present invention, describing the basic principles, main features and advantages of the present invention. However, those skilled in the art should understand that the embodiments of the present invention are not limited to the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Various changes can be made within the knowledge of ordinary technicians in this field without departing from the purpose of the embodiments of the present invention. It is not necessary and impossible to list all the embodiments here. The obvious changes or modifications derived from this are still within the scope of protection of the embodiments of the present invention.
Claims
1. A method for preparing a diatomic metal complex / CdS nanorod composite photocatalyst, characterized in that: The steps include: S1. FeCl2·4H2O and methanol are placed in a nitrogen reflux container, a boiling methanol solution containing 1,3-propylenediamine is added, and a boiling methanol solution containing 2,6-diformyl-4-methylphenol is added to obtain a mixed solution; S2. The mixed solution was heated in an oil bath by condensation reflux. After the reaction was completed, the crystalline solid was collected by suction filtration and washed with cold methanol to obtain the final product Fe2C 26 H 34 N4O4Cl2, referred to as Fe2LCl2; S3, after mixing CdS nanorods and Fe2LCl2, add ethanol, stir the reaction and then dry, and collect the composite product Fe2-CdS.
2. The method for preparing the diatomic metal complex / CdS nanorod composite photocatalyst according to claim 1, characterized in that: The preparation method of the CdS nanorods in step S3 is as follows: cadmium nitrate tetrahydrate and thiourea are added to a Teflon-lined high-pressure reactor filled with ethylenediamine as a solvent, and the high-pressure reactor is sealed and reacted in an oven after stirring. After the reaction is completed, the reaction is cooled to room temperature, washed with water and ethanol to obtain a precipitate, and dried to obtain CdS nanorods.
3. The method for preparing the diatomic metal complex / CdS nanorod composite photocatalyst according to claim 2, characterized in that: The added concentration of cadmium nitrate tetrahydrate in ethylenediamine is 0.0385-0.1155 g / ml, the added concentration of thiourea in ethylenediamine is 0.0385-0.1155 g / ml, and the mass ratio of cadmium nitrate tetrahydrate to thiourea is (0.5-3):
1.
4. The method for preparing the diatomic metal complex / CdS nanorod composite photocatalyst according to claim 2, characterized in that: During the preparation of CdS nanorods, the stirring temperature is 20-50°C and the time is 20-60 minutes; the reaction temperature is 140-160°C and the time is 24-72 hours.
5. The method for preparing the diatomic metal complex / CdS nanorod composite photocatalyst according to claim 1, characterized in that: In step S1, the amount of FeCl2·4H2O added to methanol is 0.008-0.064 g / ml.
6. The method for preparing the diatomic metal complex / CdS nanorod composite photocatalyst according to claim 1, characterized in that: In the boiling methanol solution containing 1,3-propylenediamine, the addition amount of 1,3-propylenediamine is 0.0368-0.292 ml / ml; in the boiling methanol solution containing 2,6-diformyl-4-methylphenol, the concentration of 2,6-diformyl-4-methylphenol is 0.0068-0.0526 g / ml; when preparing the mixed solution, the quantitative relationship between FeCl2·4H2O, 1,3-propylenediamine and 2,6-diformyl-4-methylphenol is 1:1:
1.
7. The method for preparing the diatomic metal complex / CdS nanorod composite photocatalyst according to claim 1, characterized in that: In step S2, the temperature of the oil bath heating is 50-80°C and the time is 2-6h; in step S3, the stirring reaction time is 6-10h and the drying temperature is 60-80°C.
8. The method for preparing the diatomic metal complex / CdS nanorod composite photocatalyst according to claim 1, characterized in that: In step S3, CdS nanorods and Fe2LCl2 are mixed in a mass ratio of (1-4):1, and ethanol is added until the concentration of CdS nanorods in ethanol is 3-5 mg / ml.
9. A diatomic metal complex / CdS nanorod composite photocatalyst prepared by the preparation method of the diatomic metal complex / CdS nanorod composite photocatalyst according to any one of claims 1 to 8, characterized in that: The composite photocatalyst consists of CdS nanorods and diatomic metal complexes loaded on the surface of the CdS nanorods; the CdS nanorods have a length of 1-3 μm and a hexagonal crystal structure; the diatomic metal complexes are block-shaped, specifically diiron atom complexes; the mass ratio of the CdS nanorods to the diatomic metal complexes is 2:1, and the two are physically composited with interface interaction.
10. Use of the diatomic metal complex / CdS nanorod composite photocatalyst according to claim 9 as a photocatalyst for photocatalytic decomposition of formic acid to produce hydrogen and carbon monoxide.
Citation Information
Patent Citations
Metal complex and use thereof
CN101415693A
Metal complex and use thereof
US20090062110A1
Modified metal complex and use thereof
US20100105909A1
Cited By
Preparation method and application of Co-COF / CdS composite material
CN121945181A
A preparation method and application of a Co-COF / CdS composite material
CN121945181B
Preparation method and application of double-cobalt-atom catalyst
CN122141767A